Associations between Sociodemographic, Body Mass Index, Body Image Perception, Physical Activity and Sleep Quality with Mental Health among University Students in Universiti Putra Malaysia during the COVID-19 Pandemic - Omar, Noraida; Farrah Haliny Kudin (Malaysian Journal of Medicine and Health Sciences, 2023)
Introduction: Mental health problem among university students during COVID-19 pandemic became one of the global main issues. There is limited study on mental health among university student during COVID-19 pandemic. Therefore, this study aimed to determine the associations between socio-demographic, body mass index, body image perception, physical activity and sleep quality with mental health among university students in Universiti Putra Malaysia. Methods: This is a cross-sectional study with a total sample of 130 students aged 18 to 25 years old which were recruited through a multistage sampling. An English online self-administered questionnaire was used to collect the data on socio-demographic characteristics, weight and height, body image perception (BSQ-8C), physical activity (GPAQ), sleep quality (PSQI), and mental health (DASS-21). Results: Majority of the respondents were female (76.2%), Malay (78.5%), in second year of study (28.5%), from low income family (59.2%) and stayed with parents during COVID-19 pandemic (57.7%). Results showed 44.6% of respondents had depressive symptoms, 56.9% had anxiety symptoms and 29.2% had stress symptoms with severity mild to extremely severe. Body mass index (r=0.205, p<0.005), body image perception (r=0.538, p<0.001), and sleep quality (r=0.460, p<0.001) were associated with depression subscale. Meanwhile, body image perception (r=0.449, p<0.001), and sleep quality (r=0.450, p<0.001) were correlated with anxiety subscale. Stress subscale was correlated with body image perception (r=0.473, p<0.001) and sleep quality (r=0.492, p<0.001). Conclusion: Affected students should be helped and referred to healthcare practitioner to ensure they able to overcome with these problems and remains healthy during this pandemic. REFERENCES World Health Organization. Mental health: Strengthening our response. 2018. Available from: https://www.who.int/news-room/fact-sheets/detail/mental-health-strengthening-our-response Malaysian Mental Health Association. Mental Health Handbook. 2019. Available from: https://www.myhealthmylife.com.my/sites/default/files/2019-12/Mental_Health_Booklet_181119.pdf Ashraful, I. M., Low, W. Y., Tong, W. T., & Yuen, C. C. W. Factors associated with depression among university students in Malaysia: A cross-sectional study. 2018:415-427. https://doi.org/10.18502/kls.v4i4.2302 [Google Scholar] Sherman, A. C., Williams, M. L., Amick, B. C., Hudson, T. J., & Messias, E. L. Mental health outcomes associated with the COVID-19 pandemic: Prevalence and risk factors in a southern US state. Psychiatry Research. 2020;293. https://doi.org/10.1016/j.psychres.2020.113476 [Google Scholar][Pubmed][Crossref] Wang, Z. H., Yang, H. L., Yang, Y. Q., Liu, D., Li, Z. H., Zhang, X. R., Zhang, Y. J., Shen, D., Chen, P. L., Song, W. Q., Wang, X. M., Wu, X. B., Yang, X. F., & Mao, C. Prevalence of anxiety and depression symptom, and the demands for psychological knowledge and interventions in college students during COVID-19 epidemic: A large cross-sectional study. Journal of Affective Disorders. 2020;275(1023):188–193. https://doi.org/10.1016/j.jad.2020.06.034 [<a href="https://scholar.google.com/scholar_lookup?title=Prevalence+of+anxiety+and+depression+symptom%2C+and+the+demands+for+psychological+knowledge+and+interventions+in+college+students+during+COVID-19+epidemic%3A+A+large+cross-sectional+study&btnG=">Google Scholar] [PMC free article] [Pubmed][Crossref] World Health Organization. Body mass index. 1998. Available from: https://www.euro.who.int/en/health-topics/disease-prevention/nutrition/a-healthy-lifestyle/body-mass-index-bmi Pook, M., Tuschen-Caffier, B., & Brähler, E. Evaluation and comparison of different versions of the Body Shape Questionnaire. Psychiatry Research. 2008;158(1):67–73. https://doi.org/10.1016/j.psychres.2006.08.002 [Google Scholar][Pubmed][Crossref] Evans, C., & Dolan, B. Body shape questionnaire: Derivation of shortened “alternate forms.” International Journal of Eating Disorders. 1993;13(3):315–321. https://doi.org/10.1002/1098-108X(199304)13:3<315::AID-EAT2260130310>3.0.CO;2-3 [Google Scholar][Pubmed] World Health Organization. Global Physical Activity Questionnaire Analysis Guide. 2002. Available from: https://www.who.int/ncds/surveillance/steps/resources/GPAQ_Analysis_Guide.pdf Buysse, D.J., Reynolds, C.F., Monk, T.H., Berman, S.R., & Kupfer, D. J. The Pittsburgh Sleep Quality Index: A new instrument for psychiatric practice and research. Psychiatry Research. 1989;28:193–213. [<a href="https://scholar.google.com/scholar_lookup?title=Buysse%2C+D.J.%2C+Reynolds%2C+C.F.%2C+Monk%2C+T.H.%2C+Berman%2C+S.R.%2C+%26+Kupfer%2C+D.+J.+The+Pittsburgh+Sleep+Quality+Index%3A+A+new+instrument+for+psychiatric+practice+and+research&btnG=">Google Scholar][Pubmed][Crossref] Lovibond, S., & Lovibond, P. Manual for the depression anxiety stress scales. 2nd ed. Sydney, N.S.W.: Psychology Foundation of Australia. 1995. [Google Scholar] Jia, Y. F., & Loo, Y. T. Prevalence and determinants of perceived stress among undergraduate students in a Malaysian university. Journal of Health and Translational Medicine. (2018);21(1):1–5. [Google Scholar] Latiff, L. A., Aszahari, M. A. A., Khalek, N. F. A., Fang, K. J., & Ibrahim, N. Prevalence of mental health problems and the associated factors among undergraduate students in a public university, Malaysia. International Journal of Public Health and Clinical Sciences. 2014;1(1):59–69. [Google Scholar] Wang, C., Pan, R., Wan, X., Tan, Y., Xu, L., Ho, C. S., & Ho, R. C. Immediate psychological responses and associated factors during the inital stage of the 2019 Coronavirus Disease (COVID-19) epidemic among the general population in China. International Journal of Environmental Research Aand Public Health. 2020;17:1–25. https://doi.org/10.1093/qjmed/hcaa110 [<a href="https://scholar.google.com/scholar_lookup?title=Immediate+psychological+responses+and+associated+factors+during+the+inital+stage+of+the+2019+Coronavirus+Disease+%28COVID-19%29+epidemic+among+the+general+population+in+China&btnG=">Google Scholar][Pubmed] Sundarasen, S., Chinna, K., Kamaludin, K., Nurunnabi, M., Baloch, G. M., Khoshaim, H. B., Hossain, S. F. A., & Sukayt, A. Psychological impact of covid-19 and lockdown among university students in malaysia: Implications and policy recommendations. International Journal of Environmental Research and Public Health. 2020;17(17):1–13. https://doi.org/10.3390/ijerph17176206 [Google Scholar][PMC free article] [Pubmed] Liu, C. H., Zhang, E., Wong, G. T. F., Hyun, S., & Hahm, H. “Chris.” Factors associated with depression, anxiety, and PTSD symptomatology during the COVID-19 pandemic: Clinical implications for U.S. young adult mental health. Psychiatry Research. 2020;290. https://doi.org/10.1016/j.psychres.2020.113172 [<a href="https://scholar.google.com/scholar_lookup?title=Factors+associated+with+depression%2C+anxiety%2C+and+PTSD+symptomatology+during+the+COVID-19+pandemic%3A+Clinical+implications+for+U.S.+young+adult+mental+health&btnG=">Google Scholar] [PMC free article] [Pubmed][Crossref] Shamsuddin, K., Fadzil, F., Ismail, W. S. W., Shah, S. A., Omar, K., Muhammad, N. A., Jaffar, A., Ismail, A., & Mahadevan, R. Correlates of depression, anxiety and stress among Malaysian university students. Asian Journal of Psychiatry. 2013;6(4):318–323. https://doi.org/10.1016/j.ajp.2013.01.014 [Google Scholar][Pubmed][Crossref] Seetan, K., Al-Zubi, M., Rubbai, Y., Athamneh, M., Khamees, A., & Radaideh, T. Impact of COVID-19 on medical students’ mental wellbeing in Jordan. Plos One. 2021;16(6):e0253295. https://doi.org/10.1371/journal.pone.0253295 [Google Scholar] [PMC free article] [Pubmed][Crossref] Rudenstine, S., McNeal, K., Schulder, T., Ettman, C. K., Hernandez, M., Gvozdieva, K., & Galea, S. Depression and Anxiety During the COVID-19 Pandemic in an Urban, Low-Income Public University Sample. Journal of Traumatic Stress. 2021;34(1):12–22. https://doi.org/10.1002/jts.22600 [Google Scholar][Pubmed] Kandasamy, N., Kolandaisamy, I., & Tukiman, N. A. Factors That Influence Mental Illness Among Students in Public Universities. Journal of Business & Economic Analysis. 2020;3(1):77–90. https://doi.org/10.36924/sbe.2020.3106 [Google Scholar] Wathelet, M., Duhem, S., Vaiva, G., Baubet, T., Habran, E., Veerapa, E., Debien, C., Molenda, S., Horn, M., Grandgenèvre, P., Notredame, C. E., & D’Hondt, F. Factors associated with mental health disorders among university students in France confined during the COVID-19 pandemic. JAMA Network Open. 2020;3(10):e2025591. https://doi.org/10.1001/jamanetworkopen.2020.25591 [Google Scholar] [PMC free article] [Pubmed] Tashakori, A., Riahi, F., & Mohammadpour, A. The relationship between body mass index and depression among high school girls in Ahvaz. Advances in Medicine. 2016:1–5. https://doi.org/10.1155/2016/3645493 [Google Scholar] [PMC free article] [Pubmed] Weinberger, N. A., Kersting, A., Riedel-Heller, S. G., & Luck-Sikorski, C. The Relationship between Weight Status and Depressive Symptoms in a Population Sample with Obesity: The Mediating Role of Appearance Evaluation. Obesity Facts. 2018;11(6):514–523. https://doi.org/10.1159/000492000 [<a href="https://scholar.google.com/scholar_lookup?title=The+Relationship+between+Weight+Status+and+Depressive+Symptoms+in+a+Population+Sample+with+Obesity%3A+The+Mediating+Role+of+Appearance+Evaluation&btnG=">Google Scholar]][Pubmed] Amir Hamzah, N. S., Nik Farid, N. D., Yahya, A., Chin, C., Su, T. T., Rampal, S. R. L., & Dahlui, M. The Prevalence and Associated Factors of Depression, Anxiety and Stress of First Year Undergraduate Students in a Public Higher Learning Institution in Malaysia. Journal of Child and Family Studies. 2019;28(12):3545–3557. https://doi.org/10.1007/s10826-019-01537-y [<a href="https://scholar.google.com/scholar_lookup?title=The+Prevalence+and+Associated+Factors+of+Depression%2C+Anxiety+and+Stress+of+First+Year+Undergraduate+Students+in+a+Public+Higher+Learning+Institution+in+Malaysia&btnG=">Google Scholar] Mokhtari, T., Jamaluddin, R., & Saad, H. A. Lifestyle and psychological factors associated with body weight status among university students in Malaysia. Pakistan Journal of Nutrition. 2015;14(1):18–28. https://doi.org/10.3923/pjn.2015.18.28 [Google Scholar] [PMC free article] [Pubmed] Mohamad, N. E., Sidik, S. M., Akhtari-Zavare, M., & Gani, N. A. The prevalence risk of anxiety and its associated factors among university students in Malaysia: a national cross-sectional study. BMC Public Health. 2021;21(1):1–12. https://doi.org/10.1186/s12889-021-10440-5 [<a href="https://scholar.google.com/scholar_lookup?title=Mohamad%2C+N.+E.%2C+Sidik%2C+S.+M.%2C+Akhtari-Zavare%2C+M.%2C+%26+Gani%2C+N.+A.+The+prevalence+risk+of+anxiety+and+its+associated+factors+among+university+students+in+Malaysia%3A+a+national+cross-sectional+study&btnG=">Google Scholar] Barnes, M., Abhyankar, P., Dimova, E., & Best, C. Associations between body dissatisfaction and self-reported anxiety and depression in otherwise healthy men: A systematic review and meta-analysis. PLoS ONE. 2020;15(2):1–24. https://doi.org/10.1371/journal.pone.0229268 [<a href="https://scholar.google.com/scholar_lookup?title=Associations+between+body+dissatisfaction+and+self-reported+anxiety+and+depression+in+otherwise+healthy+men%3A+A+systematic+review+and+meta-analysis&btnG=">Google Scholar] [PMC free article] [Pubmed] Edman, J. L., Lynch, W. C., & Yates, A. The impact of exercise performance dissatisfaction and physical exercise on symptoms of depression among college students: A gender comparison. Journal of Psychology: Interdisciplinary and Applied. 2014;148(1):23–35. https://doi.org/10.1080/00223980.2012.737871 [Google Scholar][Pubmed] Scheffers, M., van Duijn, M. A. J., Beldman, M., Bosscher, R. J., van Busschbach, J. T., & Schoevers, R. A. Body attitude, body satisfaction and body awareness in a clinical group of depressed patients: An observational study on the associations with depression severity and the influence of treatment. Journal of Affective Disorders. 2019;242:22–28. https://doi.org/10.1016/j.jad.2018.08.074 [<a href="https://scholar.google.com/scholar_lookup?title=Body+attitude%2C+body+satisfaction+and+body+awareness+in+a+clinical+group+of+depressed+patients%3A+An+observational+study+on+the+associations+with+depression+severity+and+the+influence+of+treatment&btnG=">Google Scholar][Pubmed][Crossref] Fatemeh, Y., & Esra, T. Association of stress, anxiety and depression with the body mass index and the body image perception among medical students. Archives of Nursing Practice and Care. 2021:008–014. https://doi.org/10.17352/2581-4265.000054 [Google Scholar] Giuntella, O., Hyde, K., Saccardo, S., & Sadoff, S. Lifestyle and mental health disruptions during COVID-19. Proceedings of the National Academy of Sciences of the United States of America. 2021;118(9). https://doi.org/10.1073/pnas.2016632118 [Google Scholar][Pubmed] Akhtarul Islam, M., Barna, S. D., Raihan, H., Nafiul Alam Khan, M., & Tanvir Hossain, M. Depression and anxiety among university students during the COVID-19 pandemic in Bangladesh: A web-based cross-sectional survey. PLoS ONE. 2020;15(8):1–13. https://doi.org/10.1371/journal.pone.0238162 [Google Scholar] [PMC free article] [Pubmed] Deepthi, R., Ashakiran, S., Akhilesh, T. V., & Reddy, M. Good mental health status of medical students: Is there a role for physical activity?. Journal of Krishna Institute of Medical Sciences University. 2015;4(1):55–63. [Google Scholar] Pilipović-Spasojević, O., Ponorac, N., & Spremo, M. Correlation of physical activity with stress, depression and anxiety in female students. Scripta Medica. 2020;51(4):244–251. https://doi.org/10.5937/scriptamed51-27863 [Google Scholar] Vizbaraitė, D., & Morkūnaitė, R. The effects of diet, physical activity and social factors on stress perceived by students. Baltic Journal of Sport and Health Sciences. 2017;3(106):49–53. https://doi.org/10.33607/bjshs.v3i106.33 [Google Scholar] Pensuksan, W. C., Lertmaharit, S., Lohsoonthorn, V., Rattananupong, T., Sonkprasert, T., Gelaye, B., & Williams, M. A. Relationship between poor sleep quality and psychological problems among undergraduate students in the Southern Thailand. Walailak Journal of Science and Technology. 2016;13(4):235–242. [Google Scholar] [PMC free article] [Pubmed] Rosso, A. C., Wilson, O. W. A., Papalia, Z., Duffey, M., Kline, C. E., & Bopp, M. Frequent restful sleep is associated with the absence of depressive symptoms and higher grade point average among college students. Sleep Health. 2020. https://doi.org/10.1016/j.sleh.2020.01.018 [Google Scholar][Pubmed][Crossref] Zhang, Y., Peters, A., & Bradstreet, J. Relationships among sleep quality, coping styles, and depressive symptoms among college nursing students: A multiple mediator model. Journal of Professional Nursing. 2018;34(4):320–325. https://doi.org/10.1016/j.profnurs.2017.12.004 [Google Scholar][Pubmed][Crossref] Chen, R., Liang, S., Peng, Y., Li, X., Chen, J., & Tang, S. Mental health status and change in living rhythms among college students in China during the COVID-19 pandemic : A large-scale survey. Journal of Psychosomatic Research. 2020;137. https://doi.org/10.1016/j.jpsychores.2020.110219 [Google Scholar][Pubmed][Crossref] Tang, W., Hu, T., Hu, B., Jin, C., Wang, G., Xie, C., & Chen, S. Prevalence and correlates of PTSD and depressive symptoms one month after the outbreak of the COVID-19 epidemic in a sample of home- quarantined Chinese university students. Journal of Affective Disorders. 2020;274:1–7. https://doi.org/10.1016/j.jad.2020.05.009 [<a style="background-color: #ffffff; font-size: 0.875rem;" href="https://scholar.google.com/scholar_lookup?title=Prevalence+and+correlates+of+PTSD+and+depressive+symptoms+one+month+after+the+outbreak+of+the+COVID-19+epidemic+in+a+sample+of+home-+quarantined+Chinese+university+students&btnG=">Google Scholar] [Pubmed][Crossref]